2004
DOI: 10.1021/jm040857x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-Converting Enzyme-1 Inhibition and Growth of Human Glioblastoma Cells

Abstract: Endothelin-1 (ET-1) is mitogenic and/or antiapoptotic in human cancers, and antagonists to ET-1 receptors are under evaluation for cancer treatment. Inhibition of ET-1 activation by the endothelin-converting enzymes 1(a)(-)(d) (ECE-1(a)(-)(d); EC 3.4.24.71) represents another approach to block the ET-1 effect in cancer. To evaluate this potential, we synthesized and characterized a series of low nanomolar nonpeptidic thiol-containing ECE-1 inhibitors, and evaluated their effect, as well as the effect of inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…A separate study has also reported that ECE-specific inhibitors may represent a novel therapeutic approach to human cancers. 54 Our study is the first to implicate that ECE-1 siRNA can effectively downregulate ECE-1 expression in oral SCC cells. Recent studies have demonstrated that siRNA targeting cell proliferation genes and antiapoptosis genes could provide novel therapies for cancer.…”
Section: Discussionmentioning
confidence: 65%
“…A separate study has also reported that ECE-specific inhibitors may represent a novel therapeutic approach to human cancers. 54 Our study is the first to implicate that ECE-1 siRNA can effectively downregulate ECE-1 expression in oral SCC cells. Recent studies have demonstrated that siRNA targeting cell proliferation genes and antiapoptosis genes could provide novel therapies for cancer.…”
Section: Discussionmentioning
confidence: 65%
“…Addition of exogenous ET-1 only partially recovered this effect on invasion implicating an alternative role for ECE-1 independent of ET-1 generation. A unique role for ECE-1 has also been proposed by Berger et al (2005) who demonstrated that ECE-1 inhibitors could inhibit proliferation of human glioblastoma cells without reducing ET-1 levels (Berger et al, 2005). Endothelin-converting enzyme 1a and ECE-1c isoforms were next transiently expressed in epithelial (PC-3) and stromal (STO) cells to assess their influence on invasion.…”
Section: Discussionmentioning
confidence: 98%
“…This resulted into reduced autocrine actions of ET-1 and consequently to a decrease in SCC cell proliferation [32]. Berger et al who originally reported elevated levels of ECE-1 in human glioblastomas, recently also proved a growthinhibitory effect of non-peptide ECE-1 inhibitors in glioblastoma cells [24]. To determine the potential clinical relevance of targeting ECE-1 in breast cancer, we investigated the effects of the non-peptide selective ECE-1 inhibitor RO 67-7447 on ET-1 expression in MCF-7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For all in vitro experiments, non-peptide selective ECE-1 inhibitor RO 67-7447 ((2S,4R)-4-mercapto-2-(2,4,5-trifluoro-benzyloxymethyl)-pyrrolidine-1-carboxylic acid 2-methoxycarbonyl-phenyl ester) [24] was dissolved in methanol and diluted to the particular concentration. The compound was kindly provided by F. Hoffmann-La Roche (Basel, Switzerland).…”
Section: Inhibition Of Ece-1mentioning
confidence: 99%